2015
DOI: 10.1002/tal.1217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of openings on the punching shear strength of RC flat‐plate slabs without shear reinforcement

Abstract: SUMMARYOpenings in RC flat-plate slabs are one of the critical factors that influence the punching shear strength of the slab and determine its thickness in the vicinity of the slab-column joint. This study experimentally investigates the effects of openings on the punching shear strength of flat-plate slabs without shear reinforcement. Tests were performed on eight flat-plate slab specimens considering the layout and number of openings as test variables. The failure characteristics of each specimen are examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The current design provisions are compared with the obtained FEA results of the parametric analyses and a comparison between these design provisions is made to evaluate their effectiveness to predict the punching shear strength of slabs with openings. The comparison between previously tested slabs with openings and design provisions indicates the conservatism of the design codes, with similar findings to be offered in this study. Finally, probabilistic analyses are performed using the design equations to examine the effect of different openings with randomness in material properties and distance and size of the openings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current design provisions are compared with the obtained FEA results of the parametric analyses and a comparison between these design provisions is made to evaluate their effectiveness to predict the punching shear strength of slabs with openings. The comparison between previously tested slabs with openings and design provisions indicates the conservatism of the design codes, with similar findings to be offered in this study. Finally, probabilistic analyses are performed using the design equations to examine the effect of different openings with randomness in material properties and distance and size of the openings.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete flat slabs may be vulnerable to punching shear failure, especially when due to architectural reasons openings are created next to the slab–column connection area to accommodate the utilities layout. Experimental studies of reinforced concrete flat slabs including specimens with openings performed in the 1950s and 1960s by Moe and Hognested et al Testing slabs with openings did not appear again until 1990s, where the interest in slabs with openings revived with El‐Salakawy et al and more recently with Teng et al, Bu and Polak, Borges et al, Anil et al, and Ha et al All these experimental findings have shown that when the openings are located near the column it may be critical to significantly reduce the punching shear strength of the connection. However, these experimental efforts consider only cases with openings located at a certain distance from column's face, that is, next to the column or within the critical/control perimeter.…”
Section: Introductionmentioning
confidence: 99%
“…Carsten Siburg and Josef Hegger [11] tested 13 full scale footing specimens under uniform soil stress to investigate the punching shear response of footing with practical size. Taehun Ha et al [12] studied the effect of slab opening on the punching shear capacity of RFT flat slab system. Based on test parameters such as the amount of RFT, the concrete strength, the dimensions of column, the openings, and the loading procedures, eight test specimens were tested in this study…”
Section: Fig 2 Critical Shear Perimetermentioning
confidence: 99%
“…Several researchers studied the punching shear behavior of slabs with openings, including Elstner and Hognestad [5], Moe [6], and Regan [7] and later by Gomes and Andrade [8] and El-Salakawy et al [9]. Recently, Teng et al [10], Borges et al [11], Anil et al [12], Ha et al [13], Balomenos et al [14] and Liberati et al [15] carried out studies on this topic. Despite the significant advances achieved, all these experimental findings have shown that when the openings are located near the column it may be critical to significantly reduce the punching shear strength of the connection.…”
Section: Introductionmentioning
confidence: 99%